The Effect of Leadership Style and Work Motivation on Employee Performance at PT. Alpha Ems (Enterprise Management Solution) Medan Branch - Dedy Hermanto Panjaitan (Junal Ilmu Manajemen, 2021)
This study aims to determine the effect of leadership style and work motivation on employee performance at PT. Alpha EMS (Enterprise Management Solution) Medan. The population used in this study were all employees at PT. Alpha EMS (Enterprise Management Solution) Medan Branch, and the sample used in this study were all employees at PT. Alpha EMS (Enterprise Management Solution) Medan Branch, amounting to 56 people. The data collection technique in this study was a questionnaire. This type of research is a type of associative research. The variables in this study are leadership style (X1), work motivation (X2), and employee performance (Y). The analysis technique used in this research is Multiple Linear Analysis, namely: Y – 4,243 + 0,472X1 + 0,359X2. And the hypothesis test used is the F test (simultaneous) of Fcount 10,850 > Ftable 3,170 and the ttest (partial) on the leadership style variable is 3,723 ≥ ttable 2,004, the t-test value on the work motivation variable is 2,712 ≥ ttable 2,004. The results of this study indicate that the independent variables, namely Leadership Style (X1), and Work Motivation (X2), have a positive and significant effect on Employee Performance at PT. Alpha EMS (Enterprise Management Solution) Medan Branch. The results of this study also indicate that the dominant variables affect the performance of employees at PT. Alpha EMS (Enterprise Management Solution) Medan Branch is a leadership style (X1).